Mandibular Body Reconstruction Utilizing a Three-Dimensional Custom-Made Porous Titanium Plate: A Four-Year Follow-Up Clinical Report - Carlos-Martín Ardila; Yuritza Hernández-Arenas; Efraín Álvarez-Martínez (Case Reports in Dentistry)
A clinical case of a 42-year-old woman patient, who had a mandibular reconstruction utilizing a three-dimensional (3D) custom-made porous titanium plate dental restoration, is presented. She showed a recurrence of a unicystic ameloblastoma involving the left hemimandible. The patient declined to be managed by a bone-free flap. A mandibular resection in the healthy areas was provided, followed by reconstruction utilizing a 3D custom-made porous titanium plate dental restoration with a hybrid dental prosthesis. The 3D rehabilitation was created considering slim tomodensitometric sections. The cutting guides and custom-created 3D plate were fabricated employing medical software via computer-aided design and fabricating with locations planned for healing abutments. The patient was contented with the rehabilitation, and the condition continued stable at the four-year follow-up.